Vascular Endothelium and Hypovolemic Shock - Gulati, Anil (Current Vascular Pharmacology, 2016)
Endothelium is a site of metabolic activity and has a major reservoir of multipotent stem cells. It plays a vital role in the vascular physiological, pathophysiological and reparative processes. Endothelial functions are significantly altered following hypovolemic shock due to ischemia of the endothelial cells and by reperfusion due to resuscitation with fluids. Activation of endothelial cells leads to release of vasoactive substances (nitric oxide, endothelin, platelet activating factor, prostacyclin, mitochondrial N-formyl peptide), mediators of inflammation (tumor necrosis factor , interleukins, interferons) and thrombosis. Endothelial cell apoptosis is induced following hypovolemic shock due to deprivation of oxygen required by endothelial cell mitochondria; this lack of oxygen initiates an increase in mitochondrial reactive oxygen species (ROS) and release of apoptogenic proteins. The glycocalyx structure of endothelium is compromised which causes an impairment of the protective endothelial barrier resulting in increased permeability and leakage of fluids in to the tissue causing edema. Growth factors such as angiopoetins and vascular endothelial growth factors also contribute towards pathophysiology of hypovolemic shock. Endothelium is extremely active with numerous functions, understanding these functions will provide novel targets to design therapeutic agents for the acute management of hypovolemic shock. Hypovolemic shock also occurs in conditions such as dengue shock syndrome and Ebola hemorrhagic fever, defining the role of endothelium in the pathophysiology of these conditions will provide greater insight regarding the functions of endothelial cells in vascular regulation.
Keywords: Hemorrhagic shock